Chewing and spitting: A marker of psychopathology and behavioral severity in inpatients with an eating disorder. (April 2015) - Makhzoumi, Saniha H.; Guarda, Angela S.; Schreyer, Colleen C.; Reinblatt, Shauna P.; Redgrave, Graham W.; Coughlin, Janelle W.
Abstract: Chewing and spitting out food is a frequent behavior in hospitalized patients with eating disorders (ED). Personality characteristics of those who frequently chew-spit (CHSP), the amount of food consumed during CHSP episodes, associated sense of loss of control overeating (LOC), and clinical response to hospital-based treatment have not been examined and were the focus of this study. Participants ( N = 324) were inpatients on a behavioral ED specialty unit. A third of the sample ( n = 107) reported engaging in CHSP in the 8 weeks prior to admission with 21% ( n = 69) reporting CHSP at least once per week. Those who engaged in the behavior at least weekly (CHSP +) were compared to those with less frequent or no CHSP (CHSP −) on demographic and clinical indices and on the EDI, BDI, and the NEO-FFI. Participants were also asked if their CHSP behavior involved a binge-like amount of food (≥ 1000 kcal) or was associated with LOC. The CHSP + group was more likely to have purging diagnoses. After controlling for purging diagnosis, CHSP + were found to engage in more restricting, diet pill and laxative use, and excessive exercise, and endorsed greater drive for thinness, body dissatisfaction, depression, and neuroticism than CHSP −. Among all CHSP + participants, LOC was present in 70% and a minority ( n = 10, 18%) endorsed recent CHSP on binge-like amounts of food. This behavior should be assessed routinely in all patients, as it appears associated with increased eating behavior severity and increased psychiatric comorbidity at hospital admission. Highlights: CHSP is a common behavior in eating disorders, often associated with loss of control, and can involve a binge amount of food. Patients who CHSP reported higher frequencies of ED behaviors and engaged in more ED behaviors than those who did not CHSP. Patients who CHSP reported higher drive for thinness, body dissatisfaction, depressive symptomatology, and neuroticism. Short-term hospital course did not differ between those who engaged in CHSP and those who did not.